Study on the Spiral Bevel Gear NC Machining Technology based on Double-spindle Cutter Head Machine - Xu Zengjun; Deng Jing; Chen Shichao (Jixie chuandong)
In order to improve spiral bevel gear machining efficiency and reduce installing times,the method of machining spiral bevel gear by double-spindle cutter head is proposed. Firstly,the double-spindle cutter head machine model is established,and the NC machining motion is analyzed. Secondly,the machine motion axis coordinate is calculated based on motion equivalent relation. On basis of these works,in order to ensure tooth flank machining precision,the process of tooth flank errors modification for double-spindle cutter head machining is studied. Finally,the machining and measuring experiments are conducted on a pair of 17/28 gears,and the results verifies that the machining method by double-spindle cutter head is effective.